Phylogenetic and genetic diversity of marble goby (Oxyeleotris marmorata) from the Brantas River, East Java, Indonesia - Wahyu Endra Kusuma; Bintang Rhafsyanjani; Dina Faizatin; Lunaya Zahrani; Ni Putu Anggun Larasati; Elok Amalia; Ifa Sufaichusan; Muhammad Dailami; Muhammad Nurfa’iq Hibatullah; Kiki Nur Azam Kholil (Journal of Biotropical Research and Nature Technology, 2026)
The marble goby (Oxyeleotris marmorata) is a commercially important freshwater fish in Southeast Asia with considerable potential for aquaculture development. However, information regarding its genetic diversity and phylogenetic relationships remains limited, particularly in Indonesia. This study aimed to assess the genetic diversity and phylogenetic relationships of O. marmorata populations from the Brantas River, East Java, using mitochondrial cytochrome c oxidase subunit I (COI) sequences. Specimens were collected from Malang and Kediri, and the resulting sequences were analysed together with reference sequences obtained from GenBank. Genetic diversity was evaluated using haplotype diversity (Hd), nucleotide diversity (π), haplotype network reconstruction, genetic distance analysis, and phylogenetic inference. A total of five haplotypes (H1-H5) were identified from 37 sequences. Haplotype H1 was the most common and widespread haplotype, occurring in all Indonesian populations as well as in Thailand and Cambodia. In contrast, H2 was unique to Vietnam, whereas H3-H5 were restricted to Thailand. All individuals from the Brantas River shared a single haplotype, resulting in zero haplotype diversity (Hd = 0) and nucleotide diversity (π = 0). Phylogenetic and haplotype network analyses consistently recovered two mitochondrial lineages, while genetic distances among haplotypes ranged from 0.16% to 1.69%, indicating shallow intraspecific divergence. The absence of mitochondrial variation in the Brantas River populations may reflect historical population connectivity, reduced mitochondrial variability, or past demographic events such as population bottlenecks. These findings provide baseline genetic information to support future conservation, broodstock management, and domestication programs for O. marmorata.